Implementation of Quality Management in Improving Teacher Pedagogic Competence at SMP Negeri 2 Banjaran, Bandung Regency - Muchtarom, Muchtarom; Saefurridjal, Achmad (The International Journal of Education Management and Sociology, 2023)
The purpose of this study is to determine the implementation of quality management, and teacher pedagogic competence through its stages. The research method uses a qualitative approach, which narrates pedagogical science. Data collection techniques are in-depth interviews, field observations, and documentation studies. Validation after the data is collected is then analyzed through data reduction, data presentation, and data verification, concluding. The results show that the quality management of educators and education staff at SMP Negeri 2 Banjaran, Bandung Regency is already running, but not optimal, because there are still elements that do not meet the requirements, such as (1). Analysis of HR quality management at the stages of planning, placement, development, and assessment, as well as creating harmonious relationships between school members. There is still administrative staff who are not following their areas of expertise. (2). Teachers on average already have pedagogical competence although there is still one element that has not been implemented properly, due to limited school facilities. And educational and dialogic learning, learning evaluation, in developing students to actualize their various potentials, all have been done, but the utilization of learning technology has not been maximized. (3). Efforts to improve teacher pedagogic competence at SMP Negeri 2 Banjaran, Bandung Regency, have been running because there was encouragement from the school principal to increase competence and academic qualifications in using the facilities to the fullest, but learning was still limited.